The Gaelic and Indian Origins of the American Revolution diversity and empire in the British Atlantic, 1688-1783 - Fisher, Samuel K. ca. 20./21. Jh (Oxford Academic, 2022)
The Gaelic and Indian Origins of the American Revolution offers a new way of understanding the American Revolution and the relationship between diversity and revolution in the British empire. Drawing on little-used sources in Irish and Scottish Gaelic, the book shows how people experiencing colonization in the eighteenth-century British empire-Irish-speaking Catholics, Scottish Highlanders, and Indigenous nations of North America-fought back by building relationships with the king and imperial officials. In the process, they created a more inclusive empire and triggered conflict between the imperial state and formerly privileged provincial Britons: Irish Protestants, Scottish Whigs, and American colonists. The American Revolution was only one aspect of this larger conflict between inclusive empire and the exclusionary patriots within the British empire. By putting typically excluded Gaelic and Indian voices at the center of the story and taking a comparative approach that includes Scotland and Ireland as well as North America, the book offers a new account of how empires functioned in the eighteenth century, how they fell apart, and how questions of diversity explain both. In the process it uncovers the British, imperial origins of Americans' racial dilemmas, showing how these were not new or uniquely American but instead the awkward legacies of a more complex imperial history